Analysis of occurrence of metals: Ni, Zn, Cu, Pb and Cd in oysters (Crassostrea brasiliana) and sediment collected in the Cananeia Estuary-SP (Brazil) - Barros, Danielle; Barbieri, Edison (O Mundo da Saúde, 2012)
The objective of this study was to evaluate the concentrations of trace elements, such as cadmium, lead, copper, zinc and nickel in sediments and oysters of the species Crassostrea brasiliana (bivalve quite abundant and of great economic value to the region) and taking into account that the choice of these nature may reflect specific environmental conditions and, from then on, diagnose quality for cultivation in this region, in particular in relation to food security and still provide for long and medium-term effects of disturbances. The Pb, relative to other metals analyzed, 75% of the sampled points predominated and their surface distribution 0.137 ± 0.015; 0.127 ± 0.006; 0.127 ± 0.015 and 0.030 ± 0.052 ppm, for order of points sampled. Already the concentration in oysters followed in the order Zn > Cu > Pb > Ni and Cd missing in all the samples collected